Challenges of art profession in Nigeria: History, Development and Learning - Josiah Okeke (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The development of the art profession in Nigeria has been shaped by various socio-cultural factors, including deep-rooted cultural values, traditional practices, and prevailing societal perceptions of art. Despite Nigeria's rich artistic heritage, the profession continues to face persistent challenges that hinder its growth and broader societal recognition. Objective: This study aims to examine how cultural values, traditions, and societal attitudes have influenced the development of the art profession in Nigeria. Method: The research employed a systematic literature review, involving the identification and selection of credible sources such as peer-reviewed journal articles, academic books, and authoritative online materials. The data were analyzed using thematic analysis to extract key patterns and insights. Result: The results indicate that the Nigerian art profession is confronted with significant challenges, including financial constraints, inadequate infrastructure, limited access to arts education, and a lack of public exposure. Conclusion: The study concludes that with progressive reforms and strategic support, the art profession in Nigeria has the potential to achieve greater recognition and sustainability. Contribution: This research contributes to a deeper understanding of the structural and cultural barriers faced by Nigerian artists and provides a basis for informed policy recommendations and development initiatives.